A Flexible Procedure for Adjusting Rates and Proportions, Including Statistical Methods for Group Comparisons - Clogg, Clifford C.; Eliason, Scott R. (American Sociological Review, 1988)
Clifford C. Clogg, Scott R. Eliason, A Flexible Procedure for Adjusting Rates and Proportions, Including Statistical Methods for Group Comparisons, American Sociological Review, Vol. 53, No. 2 (Apr., 1988), pp. 267-283